Planning, Conducting, and Evaluating the County Leadership Program - Elizabeth B. Bolton (EDIS)
A teaching guide produced by the Florida Cooperative Extension Service, University of Florida, Institute of Food and Agricultural Sciences. Advisory committees working with Extension County Faculty as well as other community service organizations using this guide will develop a group of local leaders with effective resolution and goal attainment skills. Original publication date March 2005.